PATIENT CLASSIFICATION AND NURSING STAFF DIMENSIONING IN A PEDIATRIC INPATIENT UNIT - Moraes, Rúbia Marcela Rodrigues; Lara, Ana Caroline de; Remedio, Eduardo Cardoso; Gaiva, Maria Aparecida Munhoz; Gentilini, Mozara Mota; Oliveira, João Lucas Campos de; Magalhães, Ana Maria Muller de (Cogitare Enfermagem, 2023)
Objective: to describe the implementation of the Patient Classification System and the dimensioning of the nursing staff in a pediatric inpatient unit. Method: a descriptive, cross-sectional, and retrospective study, carried out at a university hospital in the Midwest of Brazil. After the implementation of the Pediatric Patient Classification System, we compiled data from the classifications of the level of care complexity (N=4,639) among patients (n=608) admitted from January to December 2019. Descriptive statistical analysis was employed, including proprietary methodology for staff sizing. Results: there was a prevalence of intermediate care patients. According to the staff dimensioning, there was a surplus (+10) of mid-level workers, and the projected number of nurses (six) was compatible with the available number. Conclusion: the strategic implementation/employment of the Patient Classification System was indispensable for the pediatric nursing staffing forecast, considering that the staffing surplus found should be appreciated with caution.